Consider the following results.
991=9999^{1} = 99991=99
992=980199^{2} = 9801992=9801
993=97029999^{3} = 970299993=970299
994=9605960199^{4} = 96059601994=96059601
995=950990049999^{5} = 9509900499995=9509900499
Prove that 99n99^{n}99n ends in 99 for odd n.
Note by Abdulrahman El Shafei 6 years, 7 months ago
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
_italics_
**bold**
__bold__
- bulleted- list
1. numbered2. list
paragraph 1paragraph 2
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
This is a quote
# I indented these lines # 4 spaces, and now they show # up as a code block. print "hello world"
\(
\)
\[
\]
2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
99≡(−1)(mod100)⇒99n≡(−1)n(mod100).99\equiv(-1)\pmod{100} \Rightarrow 99^{n}\equiv(-1)^{n}\pmod{100}.99≡(−1)(mod100)⇒99n≡(−1)n(mod100).But,whenever nnn is an odd integer,(−1)n=(−1)⇒99n≡(−1)≡(99)(mod100), (-1)^{n}=(-1) \Rightarrow 99^{n}\equiv(-1)\equiv(99)\pmod{100},(−1)n=(−1)⇒99n≡(−1)≡(99)(mod100) for all odd n.n.n.
Log in to reply
Seriously. And Obviously -_- This was easy. Welll Done Adarsh Kumar
This is similar to prove that
(100−1)n≡99mod 100(100-1)^n\equiv 99 \mod 100(100−1)n≡99mod100
For nnn is an odd number.
Noticed that every term of the expansion is divisible by 100100100 except for the last term, −1-1−1. Hence we get
(100−1)n≡−1mod 100(100-1)^n\equiv -1 \mod 100(100−1)n≡−1mod100
While for nnn is an even number, a similar approach can prove that 99n99^n99n ends in 010101.
For this , let us consider two cases when nnn is odd and when it is even ,
When nnn is even :
999999 could be expressed as 100−1100-1100−1. So, we could write it as (100−1)n(100-1)^{n}(100−1)n. As in this case we have assumed nnn to be even us let us write n=2kn=2kn=2k . So we have (100−1)2k(100-1)^{2k}(100−1)2k . Now , little bit expanding it , we have , 10000+1−200)k10000+1-200)^{k}10000+1−200)k . Now taking p=10000+1p=10000+1p=10000+1 and q=−200q=-200q=−200 , we have (p+q)n(p+q)^{n}(p+q)n . Now let us prove one more result , for any (100+1)x(100+1)^{x}(100+1)x , the last two digits would be 010101 . By expanding by binomial theory , (100+1)x=100x+a1100x−1×1+....ay100×1x−1+1x(100+1)^{x} = 100^{x}+a_{1}100^{x-1} \times 1 + . . . . a_{y}100 \times 1^{x-1} + 1^{x}(100+1)x=100x+a1100x−1×1+....ay100×1x−1+1x So, expanding it will have x+1x+1x+1 terms. It is clear that the first xxx terms would have 000000 in their last as they are multiples of some powers of 100100100. But the last term will be 1. So , returning to our expansion we, would have , pn+a1pn−1q1+.....aypqn−1+qnp^{n} +a_{1}p^{n- 1} q^ {1} + . . . . . a_{y} p q^{n-1} + q ^{n}pn+a1pn−1q1+.....aypqn−1+qn Now in this we have except pnp^{n}pn all other terms would be a multiple of 100100100 as qqq is a motile of it . As we have earlier proove that the last term of pnp^{n}pn would be 1 . And , as all other terms end in 000000 , therefore 3rd two digits of the whole computation would be 010101 . So we have thus profed that any power that is even would yield a result of 01 at the end when applied to 100−1100-1100−1. Case 2 could be proved in a similar way and after proving it we would have proved the result so instead doing that long proof for case 2 also we could say that any odd number can be expressed n=2k+1n=2k+1n=2k+1 so just multiplying one more 999999 to any even power we would obtain the odd power. And multiplying the end two digits which are 010101 for any even power of 99 as we have proved , by 99 would give us 99 at the end. Hence , proved.
QED
Problem Loading...
Note Loading...
Set Loading...
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
99≡(−1)(mod100)⇒99n≡(−1)n(mod100).But,whenever n is an odd integer,(−1)n=(−1)⇒99n≡(−1)≡(99)(mod100) for all odd n.
Log in to reply
Seriously. And Obviously -_- This was easy. Welll Done Adarsh Kumar
This is similar to prove that
(100−1)n≡99mod100
For n is an odd number.
Noticed that every term of the expansion is divisible by 100 except for the last term, −1. Hence we get
(100−1)n≡−1mod100
(100−1)n≡99mod100
Log in to reply
While for n is an even number, a similar approach can prove that 99n ends in 01.
For this , let us consider two cases when n is odd and when it is even ,
When n is even :
QED